MUHASABAH DAN PERILAKU SEKS BEBAS - Ismail, Zaki (Tasamuh: Jurnal Studi Islam, 2017)
Modernist lifestyle among teenagers could potentially cause problems of various types, such as the one promiscuity in all circles, including the students who became one of the most important items in developing nation. These conditions will lead to freedom in dealing with the opposite sex, an understanding of religious concepts are believed able to provide new stimulus to the young people, in particular to adopt a positive process of modernism. So that modernization cannot be censored by any process, especially among teenagers. In the religion of Islam itself, casual sex behavior classified in fornication and adultery itself has expressly forbidden religion, as in Al-Qurâan Surat an-Nisa verse 32 Muhasabah is one of the religious aspects of Islam which is defined as an activity of self correction through introspection and keeping her from any possible human to do that is not in accordance with religious rules. In Islam, muhasabah classified in two parts, of which muhasabah performed after doing the deed and muhasabah performed after doing the deed. What is believed by the author is to minimize free sex activity among students. This phenomenon will be discussed in this article.